Kepemimpinan Autentik Dan Perilaku Inovatif: Keterikatan Kerja Sebagai Mediasi Studi Pada Sekretariat Dewan Provinsi Riau - Nugroho, Agung; Handayani, Ririn; Abdillah, M. Rasyid (CV. ITTC INDONESIA, 2021)
This research was conducted at the Civil Servants of the Riau Provincial Council Secretariat with the aim of examining the role of work engagement in mediating the relationship between authentic leadership and employee innovative behavior. The population of this study amounted to 196 employees. As for the research sample size, the authors use a table from Krejcie & Morgan, 1970 of 132 which was taken using systematic sampling. Analysis of the research data using descriptive statistics and verification analysis, as an analytical tool used Structural Equational Model which is processed with SmartPLS2 Software. The results of the analysis prove that at the Secretariat of the Riau Provincial Council, the more effective the authentic leadership, the more likely it is to increase the innovative behavior of employees; and an increase in the authentic leadership behavior of the leader accompanied by better employee engagement and innovative behavior.